Pengaruh Kompetensi, Motivasi Dan Budaya Perusahaan Terhadap Kinerja Karyawan Politeknik Swasta di Bandung - Priatna Kesumah; Dematria Pringgabayu (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
The purpose of this study to determine: 1) Competence, Motivation, Corporate Culture and Performance of Employees in the Private-owned Politechnic; 2) to determine the effect of Competence on Employee Performance, 3) to determine the effect of motivation on employee performance; 4) to determine the effect of Company Culture Employee Performance; 5) to determine the effect of Competence, Motivation and the Culture Company simultaneously on Employee Performance Private-owned Politechnic. The method is a method of research used census (population) of 121 respondents using descriptive analysis and verifikatif. From the results of descriptive analysis showed that the total effect of Competency (X1) of the Employee Performance (Y) of 26.16%, the total effect of motivation (X2) of the Employee Performance (Y) of 32.40%, and the total effect of Work Culture (X3) Performance of Employees (Y) of 25.22%. While the influence of Competence, Motivation, Corporate Culture of Performance jointly or simultaneously have the effect of a total of 83.79%.